Development of High-performance Organic Semiconductors for Flexible Electronics - Gomez, Raul; Souza, Felipe; Lima, Rafaela (Research of Scientia Naturalis, 2024)
The rapid growth of flexible and wearable electronics has driven significant research into the development of high-performance organic semiconductors. These materials offer unique advantages, such as mechanical flexibility, solution processability, and tunable electronic properties, making them attractive alternatives to traditional inorganic semiconductors for next-generation flexible devices. Understanding the recent advancements in organic semiconductor design and fabrication is crucial for realizing the full potential of flexible electronics. This review article aims to provide a comprehensive overview of the latest progress in the development of high-performance organic semiconductors for flexible electronics applications. The study investigates the design principles, synthesis techniques, and device integration strategies that have enabled the realization of flexible and conformable organic electronic systems with enhanced performance and reliability. The research methodology involves an extensive literature review of peer-reviewed journal articles, conference proceedings, and patent documents published within the last five years. The analysis focuses on the most promising organic semiconductor materials, their structural and electronic properties, and their implementation in diverse flexible electronic devices, such as displays, sensors, and energy storage systems. The review highlights the successful development of novel organic semiconductor architectures, including small molecules, conjugated polymers, and hybrid organic-inorganic materials, which have demonstrated superior charge transport, optical, and mechanical properties. Significant advancements in synthetic strategies, molecular engineering, and thin-film deposition techniques have enabled the fabrication of high-mobility, stable, and solution-processable organic semiconductors. The study concludes that the continued progress in organic semiconductor research holds great promise for realizing the full potential of flexible electronics. The insights gained from this review can guide future research directions and facilitate the translation of organic semiconductor innovations into practical, large-area flexible and wearable devices.